Design, synthesis and biological evaluation of β-peptoid-capped HDAC inhibitors with anti-neuroblastoma and anti-glioblastoma activity. Issue 7 (8th November 2018) - Reßing, Nina; Marquardt, Viktoria; Gertzen, Christoph G. W.; Schöler, Andrea; Schramm, Alexander; Kurz, Thomas; Gohlke, Holger; Aigner, Achim; Remke, Marc; Hansen, Finn K.
Abstract : Novel β-peptoid-capped HDAC inhibitors with anti-neuroblastoma and anti-glioblastoma activity were synthesized. Abstract : Histone deacetylases (HDACs) have been identified as promising epigenetic drug targets for the treatment of neuroblastoma and glioblastoma. In this work, we have rationally designed a novel class of peptoid-based histone deacetylase inhibitors (HDACi). A mini library of β-peptoid-capped HDACi was synthesized using a four-step protocol. All compounds were screened in biochemical assays for their inhibition of HDAC1 and HDAC6 and docking studies were performed to rationalize the observed selectivity profile. The synthesized compounds were further examined for tumor cell-inhibitory activity against a panel of neuroblastoma and glioblastoma cell lines. In particular, non-selective compounds with potent activity against HDAC1 and HDAC6 showed strong antiproliferative effects. The most promising HDACi, compound6i, displayed submicromolar tumor cell-inhibitory potential (IC50 : 0.21–0.67 μM) against all five cancer cell lines investigated and exceeded the activity of the FDA-approved HDACi vorinostat.